Pembinaan Potensi Ekonomi Kreatif melalui Pendekatan Kelembagaan - Habibullah Jimad; Roslina Roslina; Yuniar Aviati Syarif; Endro P Wahono (Jurnal Pemberdayaan Ekonomi, 2022)
Purpose: This activity aims to increase public understanding and knowledge about community empowerment through fostering creative economic potential by utilizing existing Â institutions in the village. Methods: The methods used in this community service activity are training, mentoring and consultation, also monitoring and evaluating. Results: The activity can increase participants' knowledge about the creative economy potential that can be utilized by the community, increase public awareness to play an active role through empowerment and optimal utilization of the village institutions to improve the economy and achieve the citizens' welfare of Penengahan Village, Way Khilau, Pesawaran. The training activities carried out succeeded in increasing public understanding of the creative economy potential through village institutions. Mentoring activities are needed to continue motivating the trainees and providing alternatives and solutions for the community to face their problems. Contribution: This activity helps to strengthen the capacity of the village institutions and the dynamic interaction between the managers of the village institutions and the village community